Penggunaan Media Corong Berhitug Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Matematika di Kelas II Sekolah Dasar Negeri 37 Pekanbaru - iin gusmana iin; Mimi Haryani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
This research aimed to increase of student learning achievement through the use of CorongBerhitung mediaon Mathematics subject at the second grade of State Elementary School 37 Pekanbaru, Tampan District. This research was instigated by the low of student learning achievement that could not reach the minimum standard of passing grade determined 75. This research was a Classroom Action Research. The subjects of this research were the teachers and students, and the objects were theuse of CorongBerhitung media and learning achievement.This research was conducted for two cycles, and every cycle comprised two meetingswith several steps-planning/preparing the action, implementing, observing, and reflecting. Observation, learning achievement test, and documentation were the techniques of collecting the data. The technique of analyzing the data was Descriptive analysis that was started from obtaining, arranging, processing, presenting, and analyzing the numerical data to get the description of a symptom, event or situation.Based on the research findings, the use of CorongBerhitung media could increase student learning achievement. It was known that the mean was 55.56% before the action and it was on less than 60% interval that was on poor category. After implementing the media in the first cycle, the student learning achievement increased to 75% that was on 70%-79% interval and it was on enough category. In the second cycle, the student learning achievement increased to 100% that was on 90%-100% interval and it was on very good category. Thus, it could be concluded that the use of CorongBerhitung media could increase student learning achievementat the second grade of State Elementary School 37 Pekanbaru, Tampan District.